2000
DOI: 10.1159/000053245
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Deceleration in Growth as an Early Sign of Delayed Puberty in Boys

Abstract: Objective: To describe the prepubertal growth pattern in boys with delayed puberty. Methods: Growth curves for height and height velocity covering the age range 4–14 years were constructed on the basis of retrospectively obtained data in 85 boys with delayed puberty, who attained a normal final height. Results: Between the age of 4 and 14 years the height in this cohort progressively deviated from the normal reference. At the age of 4 years, the height SDS was already significantly lower (median –0.8; p < 0.00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
21
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 26 publications
6
21
0
Order By: Relevance
“…In a study of 49 CDGP patients, 3 boys who failed to reach adult stature within TH (FH from 8.6 to 11 cm below TH) were the smallest at diagnosis [8]. Two previous studies have demonstrated that height SD reduction already after 4 or 6 years of age does not adversely affect FH [4, 5]. In both of these studies, however, the reduction of height SD before puberty was smaller and occurred later than in our study, and no comparison with boys who did not have an early childhood height SD reduction was made.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of 49 CDGP patients, 3 boys who failed to reach adult stature within TH (FH from 8.6 to 11 cm below TH) were the smallest at diagnosis [8]. Two previous studies have demonstrated that height SD reduction already after 4 or 6 years of age does not adversely affect FH [4, 5]. In both of these studies, however, the reduction of height SD before puberty was smaller and occurred later than in our study, and no comparison with boys who did not have an early childhood height SD reduction was made.…”
Section: Discussionmentioning
confidence: 99%
“…When such adolescents are compared with adolescents with normal timing of puberty, this pattern of growth will inevitably cause a reduction of relative height (standard deviations, SDs, in height) in pubertal years [1,2,3]. At least in a subgroup of CDGP subjects, the reduction in height SDs starts already early in childhood, well before puberty [4, 5]. Although boys with CDGP may be short during pubertal years, many will achieve a final adult height (FH) that is normal compared with the general population [5,6,7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…There is still no consensus on the issue whether boys with a delayed puberty reach a final height appropriate for their target height [1, 2,7,8,9,10,11,12,13]. Most authors found that boys with pubertal delay reach a final height appropriate for their parental centiles, while others claim final height was significantly below target height [6,7,8,9,10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Most authors found that boys with pubertal delay reach a final height appropriate for their parental centiles, while others claim final height was significantly below target height [6,7,8,9,10,11,12,13]. This discrepancy can partially be explained by the fact that most studied groups were a mixture of boys with a physiological delayed puberty with a normal height potential and boys with genetic short stature combined with pubertal delay.…”
Section: Introductionmentioning
confidence: 99%
“…Total inositol phosphate and phosphorylation of extracellular signal-regulated kinase were measured at various points after stimulation with increasing levels of kisspeptin. 15 (For details, see the Methods section of the Supplementary Appendix.) R e sult s…”
Section: Studies Of Gpr54 Signalingmentioning
confidence: 99%